Técnicas de estudio para la asimilación comprensiva de los conocimientos en la asignatura de estudios sociales del sexto año paralelo “b” de educación general básica de la unidad educativa “Roberto Alfredo Arregui Chauvin” ubicada en la provincia de Bolívar cantón Guaranda en el año lectivo 2021-2022 - Chiliquinga Pullotasig, Byron Xavier (2022)
This research project addressed the topic: study techniques for the comprehensive assimilation of knowledge in the subject of social studies, because most of the students and teachers in this research have little mastery and knowledge about study techniques, consequently, the student is prone to have low levels of motivation to study, in the same way the teacher would not get good results in the teaching-learning process of their students. The main objective of this project was to recognize the importance of study techniques in the comprehensive assimilation of knowledge in the subject of social studies. A mixed or multimodal descriptive methodology was used, which together enrich the research with quantitative-qualitative data and extensive theoretical documentation. According to the analysis and interpretation carried out, it was possible to collect representative data in accordance with the objectives and problems of the research, which allowed concluding that in the sixth year of EGB parallel "B" of the Educational Unit "Roberto Alfredo Arregui Chauvin" there is a deficit in the knowledge, mastery and application of study techniques in students and teachers, therefore, the processes of comprehensive assimilation of knowledge in the subject of social studies have a connotation of deficient both in teaching and learning.